2017
DOI: 10.3171/2016.2.jns152370
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of the choroidal artery in the treatment of cerebral arteriovenous malformations

Abstract: OBJECTIVE The anterior and posterior choroidal arteries are often recruited to supply arteriovenous malformations (AVMs) involving important paraventricular structures, such as the basal ganglia, internal capsule, optic radiation, lateral geniculate body, and medial temporal lobe. Endovascular embolization through these arteries is theoretically dangerous because they supply eloquent territories, are of small caliber, and lack collaterals. This study aimed to investigate the safety and efficacy of embolization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 21 publications
(24 reference statements)
1
35
0
Order By: Relevance
“…However, even following this recommendation, the risks of ischemia are high. For instance, in 2017, Elkordy et al performed 8 embolizations of ruptured AVMs through the AChA; among these cases, 2 patients suffered persistent hemiparesis 72 . Approximately 38% of capsulo-thalamic arteries arising from the AChA originate from the first part of the plexal segment, and this variation could be an important risk factor 73 .…”
Section: Arteriovenous Malformationsmentioning
confidence: 99%
“…However, even following this recommendation, the risks of ischemia are high. For instance, in 2017, Elkordy et al performed 8 embolizations of ruptured AVMs through the AChA; among these cases, 2 patients suffered persistent hemiparesis 72 . Approximately 38% of capsulo-thalamic arteries arising from the AChA originate from the first part of the plexal segment, and this variation could be an important risk factor 73 .…”
Section: Arteriovenous Malformationsmentioning
confidence: 99%
“…However, it has been recognized that embolization of feeders originating from the choroidal arteries carries considerable risk of ischemic complications, and superselective embolization has been attempted only by some experts. 4 , 15 17) In the present case, we thought that it would be possible to occlude most of feeders microsurgically with less risk than attempting endovascular feeder embolization.…”
Section: Discussionmentioning
confidence: 81%
“…It is generally considered that branches of the anterior choroidal artery supplying eloquent territories arise from the cisternal segment. 4 , 16 , 17) On the contrary, Fernandez-Miranda et al have reported that 38% of the capsulothalamic artery originated from the first part of the plexal segment in a cadaveric study. 18) To safely occlude feeding arteries originating from choroidal arteries, intraoperative MEP monitoring would be recommended even when such an attempt is carried out distal to the plexal point.…”
Section: Discussionmentioning
confidence: 94%
“…Embolizations performed from the cisternal AChoA segment frequently complicate with ischemic stroke. In one recent study on choroidal AVM embolization, two of four patients in whom embolization was performed from the cisternal segment of the AChoA, proximal to the plexal point, developed symptomatic infarction of the posterior limb of the internal capsule, with morbidity in one case (Elkordy et al 2017). Overall, 2/5 cases treated with nBCA and 2/8 cases treated with Onyx developed ischemic complications (Elkordy et al 2017).…”
Section: Discussionmentioning
confidence: 99%